L'exil irakien à Damas - Mohamed Kamel Doraï (EchoGéo)
Since the fall of Saddam Hussein regime, the conflict in Iraq is still ongoing and hundreds of thousands of Iraqis have been constrained to leave their country to move in great number towards Syria. The vast majority comes from the main cities in Iraq, and especially from Baghdad, and they settled in the suburbs of the Syrian capital. Neither Syria, nor the United Nations High Commissioner for Refugees have opened camps to accommodate the refugees, who are today one of the most important group of urban refugees throughout the world. This article analyzes the modes of settlement of the Iraqis in Damascus, and the role played by the city in the migratory dynamics of the Iraqi Diaspora.